Parent and teacher perceptions of emerging special health care needs - Kvalsvig, Amanda; Quach, Jon; Rosema, Stefanie; Goldfeld, Sharon; Quach, J; O'Connor, Meredith (My University, 2016)
Aim: A fifth of children enter school with special health care needs (SHCN) impacting on their physical, psychosocial or educational development, including many with emerging SHCN who often do not qualify for additional supports. This study aimed to compare the perceptions of parents and teachers on children’s emerging SHCN, and explore correlates of conflicting reports. Methods: The Longitudinal Study of Australian Children (LSAC) is a nationally representative study of Australian children, which includes the abbreviated Children with Special Health Care Needs Screener. Data were analysed from a subsample of n = 720 children from the LSAC Kindergarten cohort (n = 4983) for whom teachers also completed the Australian Early Development Index checklist, a measure of early childhood development that includes teacher reported SHCN. Results: Teachers (n = 120, 17.34%) identified more emerging SHCN than parents (n = 74, 10.74%), and reports were often discrepant. Children were more likely to have consistent reports of emerging SHCN when their parents had high levels of involvement at school (OR 4.86; 95% CI 1.08–21.80; P < 0.05), whereas children who came from disadvantaged family backgrounds were more likely to have teacher-only identified difficulties (OR 3.66; 95% CI 1.17–11.50; P < 0.05). Conclusion: Parents and teachers bring different perspectives to children’s development and additional support needs, each of which is valuable. Greater attention should be given to ensuring that common understandings about a child’s needs at school are established early in children’s educational pathways.
Keywords: Health -- Medical conditions; Health -- Disability; Health and wellbeing; Health; Medical conditions; Disability; Health and wellbeing